2015
DOI: 10.15302/j-fase-2015061
|View full text |Cite
|
Sign up to set email alerts
|

Lodging resistance and yield potential of winter wheat: effect of planting density and genotype

Abstract: Improved lodging resistance is important for achieving high yield in irrigated environments. This study was conducted to determine genotypic variation in lodging resistance and related morphological traits among winter wheat cultivars planted at two densities, and to identify key traits associated with lodging resistance. Lodging performance of 28 genotypes, including 24 released cultivars and four advanced lines, was evaluated at 250 plants per square meter and 500 plants per square meter in Shandong province… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
2
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 29 publications
(63 reference statements)
1
27
2
5
Order By: Relevance
“…Lodging had a consistently negative effect on crop growth [17], sugar accumulation [11] and seed yield [18]. In the present paper, for the first time, the effect of lodging on the plant growth, sugar accumulation and photosynthetic parameter of sweet sorghum when cultivated in the saline-alkali soil was investigated.…”
Section: Discussionmentioning
confidence: 83%
“…Lodging had a consistently negative effect on crop growth [17], sugar accumulation [11] and seed yield [18]. In the present paper, for the first time, the effect of lodging on the plant growth, sugar accumulation and photosynthetic parameter of sweet sorghum when cultivated in the saline-alkali soil was investigated.…”
Section: Discussionmentioning
confidence: 83%
“…Another investigation showed that decreasing plant density improved the structure of sclerenchyma and vascular bundles by increasing lignification, thus resulting in more lignin deposited in the secondary cell walls and stronger lodging resistances (Zheng et al, 2017). The mechanical strength of winter wheat stems can be modified by the lignin content (Xiao et al, 2015). Transcriptomic analyses in Brassica napus L. of lodging resistance traits showed that the upregulated genes were mainly involved in glycoside catabolic processes (especially glucosinolate catabolism) and cell wall biogenesis, whereas downregulated genes were involved in glucosinolate biosynthesis, indicating that crosstalk exists between glucosinolate metabolic processes and lignin biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…4D, Table 2). This approach has been applied to winter wheat (Xiao et al, 2015), canola (Wu and Ma, 2016), and rice (Kashiwagi and Ishimaru, 2004). Interestingly, this approach is very similar to the bending tests used to assess stalk lodging, varying only in the placement of the device lower on the stem and closer to the soil surface.…”
Section: Methods To Evaluate Root Lodgingmentioning
confidence: 99%
“…Interestingly, this approach is very similar to the bending tests used to assess stalk lodging, varying only in the placement of the device lower on the stem and closer to the soil surface. Although this approach is often presented as a measure of root anchorage, one study notes that it is difficult to separate this measure as indicative of root lodging distinct from stalk lodging (Xiao et al, 2015). For example, in rice the bending moment calculated from prostrate testing of the lowest internodes was highly predictive of Blaster‐induced stalk lodging (Shrestha et al, 2020).…”
Section: Methods To Evaluate Root Lodgingmentioning
confidence: 99%